Development of Perineal Electric Massager Experience (Pem-X) to Improve Perineal Elasticity - Suryani Manurung; Amalia Mely; Yetty Mariani Tambun (Fakultas Ilmu Keperawatan Universitas Indonesia, 2026)
Perineal injury remains a common concern in vaginal childbirth, with a prevalence of 30.6%. Low maternal perineal massage practice is a contributing factor to decreased perineal elasticity and an increased risk of perineal trauma. This pilot study aimed to develop the Perineal Electric Massager Experience (PEM-X) to support mothers in self-guided perineal massage. The research employed a level 4 Research and Development (R&D) method with a one-group pretest-posttest design. The study sample consisted of two parts: the PEM-X prototype and postpartum mothers who had vaginal deliveries. A purposive sampling technique was used to recruit 10 postpartum mothers who had vaginal deliveries for preliminary testing of the device. The device was developed at the Mechatronics Laboratory, with functional testing conducted at the Electromedical Laboratory of Health Polytechnic of the Ministry of Health Jakarta II and the Maternity Laboratory of Health Polytechnic of the Ministry of Health Jakarta I. During the intervention phase, participants used the PEM-X to massage the perineum independently according to the developed protocol. Field testing was conducted at Lebak Bulus Public Health Center. Data were analyzed using descriptive statistics and paired t-tests. The results showed that the PEM-X device operated stably and functioned well. Preliminary findings demonstrated increased perineal elasticity after device use, along with high user satisfaction in terms of comfort and ease of use. In conclusion, the innovative PEM-X device enhances perineal elasticity and has the potential to reduce perineal injury during childbirth. Further studies with a larger sample size are recommended.